Implementing design thinking to drive innovation in technical design. Issue 3 (3rd July 2022) - Eisenbart, Boris; Bouwman, S.; Voorendt, J.; McKillagan, S.; Kuys, B.; Ranscombe, C.
ABSTRACT: Design Thinking has been gaining attention over the past decade with more and more companies seeking to use it as a human-centered problem-solving approach that can create novel solutions and foster (radical) innovation. Following several success stories from business, management or even civic service delivery environment, where Design Thinking has produced highly impactful and popularized innovation, technically oriented companies have increasingly shown interest in using it to nurture their innovation and creative capabilities. In this article, a qualitative analysis of semi-structured interviews with experts applying and researching Design Thinking are presented in the context of technology-focused organizations. Several concrete insights are derived to reveal specific success factors, central characteristics, tools and methods, but also limitations and prerequisites for its effective application in such contexts. Finally, the study highlights potential adaptations of the approach to support its integration with the processes similar organizations apply in their routine practices.